2017
DOI: 10.1002/jbm.b.33940
|View full text |Cite
|
Sign up to set email alerts
|

SEM imaging of the stimulatory response of RAW264.7 cells against Porphyromonas gingivalis using a simple technique employing new conductive materials

Abstract: In the medical biology, it is essential to understand not only biological morphology but also the interaction between biological materials and agents. To study these, electron microscopy (EM) is often utilized. However, sample preparation techniques for EM require a high level of skill and a considerable time. Here, we conducted EM using a simple technique employing a conductive liquid, BEL-1, and compared the results with another simple technique employing an ionic liquid, 1-butyl-3-methylimidazolium tetraflu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The cell surface exhibited a negative electrostatic charge attributed to the presence of glycoproteins on the membrane. Upon stimulation, the cell surface underwent a transition from smooth to rough and experienced a reduction in mucus secretion [ 30 , 31 ]. The microscopic interactions between micro/nanosized MMT and human colon-associated cells or human skin-associated cells indicated that these side effects were correlated with the size distribution.…”
Section: Resultsmentioning
confidence: 99%
“…The cell surface exhibited a negative electrostatic charge attributed to the presence of glycoproteins on the membrane. Upon stimulation, the cell surface underwent a transition from smooth to rough and experienced a reduction in mucus secretion [ 30 , 31 ]. The microscopic interactions between micro/nanosized MMT and human colon-associated cells or human skin-associated cells indicated that these side effects were correlated with the size distribution.…”
Section: Resultsmentioning
confidence: 99%
“…Other solution-based methods, such as ionic liquids and BEL-1, have been used for SEM specimen procedures (Kuwabata et al 2006 ; Takahashi et al 2018 ). Despite the wide use of ionic liquids for SEM imaging, we have to be cautious about the toxicity of ionic liquids to organisms (Gonçalves et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%